Palace of treason [compact disc, unabridged] : a novel - Matthews, Jason, 1951-2021- (Simon & Schuster Audio, 2015)
Captain Dominika Egorova of the Russian Intelligence Service (SVR) has returned from the West to Moscow. She despises the men she serves, the oligarchs, and crooks, and thugs of Putin's Russia. What no one knows is that Dominika is working for the CIA as Washington's most sensitive penetration of SVR and the Kremlin.